Utilization of Black Rice Var Wojalaka with Lemongrass Essential Oil as a Face Mask - Ghello, Jennilien Merinda; Arpiwi, Ni Luh; Sukmaningsih, A. A. S. Alit (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Black rice contains antioxidants that neutralize free radicals, helping prevent wrinkles and skin damage. Fragrant lemongrass produces essential oils with citronellal, geraniol, and citronellol, which have antibacterial effects. This study aims to develop and evaluate a face mask combining black rice extract and citronella essential oil to nourish, cleanse, and tighten the skin. Masks were formulated with black rice concentrations of 30%, 40%, and 50%. Evaluations included phytochemical screening, antioxidant activity (DPPH assay), organoleptic properties, pH, homogeneity, dispersibility, and physical stability. Black rice extract showed antioxidant content of 0.037 mg/L, while the mask formulations exhibited strong antioxidant activity at 2.231 mg/L. The FII mask met Indonesian National Standard (SNI) criteria for physical stability. Clinical tests from week 2 to 6 on volunteers revealed that the FIII mask improved skin firmness, reduced acne and black spots, and increased moisture. This research demonstrates that combining black rice antioxidants with citronella essential oil produces an effective natural face mask that enhances skin health.